Activities for the local community – the level of satisfaction and the assessment of sport and recreation activities of Wroclaw program „Community Sports Coach” concerning health promotion and addiction prevention - Surynt, Agnieszka; Kulmatycki, Lesław (Polish Journal of Public Health, 2009)
Introduction. In accordance with the concept of health promotion, local authorities intend more frequently to provide constructive recommendations to certain groups of inhabitants, children and teenagers in particular, and they find it extremely beneficial to combine leisure proposals with prophylactic activities. Such functions are fulfilled by ongoing programmes, such as Street Workers, Neighbourhood Watch or Peer Youth Workers. Since 2003, the „Community Sports Coach” Programme, implemented by the Municipality of Wrocław and supervised by School Sports Association, has been realised to accomplish such goals in Wrocław. It was chosen as the leading programme in a competition released for various agendas dealing with health promotion and addiction prevention. Since 2006, the programme has been the subject of scientific analysis. Aim. The aim of the paper is to present the assessment of sporting activities and the level of satisfaction derived from participating in them, within all developmental phases of the programme under research, in 2006-2008.Material, methods and research schedule. The study comprised a group of participants of health promotion and prevention program. For the purpose of the programme analysis, the following set of principal tools was applied: U sheet,T-1 sheet, T-2 sheet and O sheet. The research was scheduled in places were sporting activities took place: on school yards and sport fields in districts of Wrocław. On the turn of October and November 2006, preliminary assessment was made. Second research cycle was held in 2007, and third – in 2008, both on the turn of September and October in successive years.Conclusions. Democratization of the whole process can be noticed very clearly in the Wrocław proposal. Participants feel responsible for activities and have a confidence of creating them.